Self-assembled collagen-like-peptide implants as alternatives to human donor corneal transplantation. Issue 61 (9th June 2016) - Islam, M. Mirazul; Ravichandran, R.; Olsen, D.; Ljunggren, M. K.; Fagerholm, Per; Lee, C. J.; Griffith, M.; Phopase, J.
Abstract : PEG-conjugated collagen-like peptides promote corneal regeneration in a pig cornea. Abstract : Extracellular matrix proteins like collagen promote regeneration as implants in clinical studies. However, collagens are large and unwieldy proteins, making small functional peptide analogs potentially ideal substitutes. Self-assembling collagen-like-peptides conjugated with PEG-maleimide were assembled into hydrogels. When tested pre-clinically as corneal implants in mini-pigs, they promoted cell and nerve regeneration, forming neo-corneas structurally and functionally similar to natural corneas.